2018
DOI: 10.1177/1744806918755283
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of Simplified Chinese version of the Pain Catastrophizing Scale in chronic pain patients: Education may matter

Abstract: ObjectivePain catastrophizing is linked to many aspects of pain perception and defines a unique dimension in predicting pain intensity and physical disability. Pain Catastrophizing Scale (PCS) is an effective, validated,self-report measure, commonly used in clinical trials. Here, we present a Simplified Chinese PCS (SC-PCS) version developed in Chinese patients suffering from chronic pain.MethodsThe SC-PCS was generated in five steps and tested on an initial patient cohort (N = 30). A convenience sample (N = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 52 publications
11
20
0
Order By: Relevance
“…However, we obtained lower alpha coe cients for the rumination (α = 0.69) and magni cation (α = 0.41) subscales but su cient for the helplessness subscale (α = 0.78). Consistent with our ndings, most previous studies [37,40,43,76,82] found lower alpha coe cients for the magni cation subscales, which could be attributed to the small number of items peculiar with the three-factor structure. It is important to note that increasing the number of scale items typically increases the Cronbach's alpha [86].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, we obtained lower alpha coe cients for the rumination (α = 0.69) and magni cation (α = 0.41) subscales but su cient for the helplessness subscale (α = 0.78). Consistent with our ndings, most previous studies [37,40,43,76,82] found lower alpha coe cients for the magni cation subscales, which could be attributed to the small number of items peculiar with the three-factor structure. It is important to note that increasing the number of scale items typically increases the Cronbach's alpha [86].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the CFA suggests that the three-factor structure had the best t for our sample compared to the one-factor or two-factor structure obtained for the English version as indicated by a low SRMR and RMSEA and high CFI and TLI. This nding is similar to the reports of many validations conducted in different samples of individuals with chronic pain [39,79,80,82]. On the contrary, other validations found the two-factor structure of the PCS to exhibit adequate model t [48,77].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In its original format the PCS comprises 13 items that are rated from 0 to 4 with the endpoints 0 (“Never”) to 4 (“All the time”). Repeatedly, results from previous studies illustrate that pain catastrophizing as assessed by the PCS comprise three factors labeled: (a) Helplessness , which pertains to the helplessness felt in situations when pain is present; (b) Rumination , that concerns the tendency to be increasingly vigilant toward pain; and (c) Magnification , which captures the tendency to exaggerate the threat value of pain . In the original study by Sullivan, were the oblique three‐factor model was proposed, the correlation between the three subscales was moderate, and the internal consistency was adequate as represented by a Cronbach's α of 0.87 for the total scale.…”
Section: Methodsmentioning
confidence: 99%
“…The subjective psychological experiences and accompanying behaviors that constitute catastrophizing are most commonly assessed with self‐report measures, and the Pain Catastrophizing Scale (PCS) is one of the most widely used questionnaires. The PCS has been validated in a number of languages and for a number of pain populations for adults . However, thus far, no study has evaluated the validity and reliability of a Swedish version of the scale.…”
Section: Introductionmentioning
confidence: 99%